Recurrent fires and environment shape the vegetation in Quercus suber L. woodlands and maquis. - Schaffhauser, Alice; Curt, Thomas; Véla, Errol; Tatoni, Thierry (Comptes rendus biologies, 2012)
The effects of fire recurrence on vegetation patterns in Quercus suber L. and Erica-Cistus communities in Mediterranean fire-prone ecosystems of south-eastern France were examined on stands belonging to 5 fire classes, corresponding to different numbers of fires (from 0 to 4) and time intervals between fires since 1959. A common pool of species was identified among the plots, which was typical of both open and closed maquis. Fire recurrence reduced the abundance of trees and herbs, whereas it increased the abundance of small shrubs. Richness differed significantly between the most contrasting classes of fire recurrence, with maximal values found in control plots and minimal values in plots that had burned recurrently and recently. Equitability indices did not vary significantly, in contrast to Shannon's diversity index which mostly correlated with richness. Forest ecosystems that have burnt once or twice in the last 50 years were resilient; that is to say they recovered a biomass and composition similar to that of the pre-fire state. However, after more than 3-4 fires, shrubland communities displayed lower species richness and diversity indices than unburned plots. The time since the last fire and the number of fires were the most explanatory fire variables, governing the structure of post-fire plant communities. However, environmental factors, such as slope or exposure, also made a significant contribution. Higher rates of fire recurrence can affect the persistence or expansion of shrublands in the future, as observed in other Mediterranean areas.
The following values have no corresponding Zotero field: accession-num: 22721564
Keywords: Acidic soil; biomass; climate; cork-oak; Ecosystem; Erica arborea L.; Fire recurrence; Fires; France; Mediterranean Region; Plant communities; Plants; Plants: classification; Quercus; Seasons; Species Specificity; Trees

Fire-vegetation interplay in a mosaic structure of Quercus suber woodlands and Mediterranean maquis under recurrent fires - Schaffhauser, a.; Curt, T; Tatoni, T (Forest Ecology and Management, 2011)
We examined the effects of ﬁre recurrence on a mosaic structure of Quercus suber and Erica-Cistus shrubland communities of Southeastern France in order to improve the understanding of ﬁre-vegetation interplay. Plant communities that were similar in 1959 (woodlands on shrublands called maquis on acidic soils) were compared along a gradient of ﬁre recurrence, from 0 to 4 ﬁres, with different time intervals between ﬁres. The results showed that understory cover increased roughly with ﬁre recurrence, whereas tree height, cover, density, stand basal area and litter depth decreased. Different ﬁre recurrences along the past decades led to different vegetation types. High ﬁre recurrence corresponded to maquis and sparse cork-oak woodlands while pure oak woodlands established in the absence of ﬁre during the same period. In all, the diversity of tree diameter decreased with ﬁre recurrence. High ﬁre recurrence (3 or 4 ﬁres in 50 years) led to a simple vertical structure of vegetation with a mono-layered shrub cover and few Quercus suber trees. In contrast, spatial connections between plants were maximal at longer time intervals, leading to a multi-layered vegetation. We ﬁnally discuss the potential implications of past ﬁres on the behavior of future ﬁres in the perspective of a sustainable management of these Mediterranean ecosystems.
Keywords: Acidic soils; Cork oak woodlands (Quercus suber L.); Fire recurrence; Maquis; Structural diversity

Soil organic matter quality and microbial catabolic functions along a gradient of wildfire history in a Mediterranean ecosystem - Guénon, René; Vennetier, Michel; Dupuy, Nathalie; Ziarelli, Fabio; Gros, Raphaël (Applied Soil Ecology, 2011)
The principal aim of this research was to determine the inﬂuence of an increasing wildﬁre history on the recovery at short and long term of soil organic matter (SOM) composition and microbial properties. The contemporary wildﬁre events (since 1950) were recorded for 27 plots located on the siliceous part of the French Mediterranean region (Maures mountain ranges). A wildﬁre history index was built, tested and calculated in order to display numerical values representative of the different wildﬁre history parameters (i.e. number of ﬁres, time since ﬁre and mean ﬁre interval). Microbial basal respiration and biomass were analysed as well as intensity of the use of 31 C-substrates, catabolic diversity and C-substrates utilisation proﬁles. Furthermore, a qualitative characterisation of the SOM was carried out by solid state 13 C NMR. Potential drivers of the microbial recovery were identiﬁed by studying the relationships between microbial activities and chemical functions of SOM. Our results showed that ﬁre histories resulting in considerable losses or alterations of SOM, such as recent or close ﬁres, decreased the microbial catabolic evenness. This could be attributed to a preferential utilisation of N-containing compounds and complex substrates such as aromatic and polymers reﬂecting a greater N microbial demand and a selection of speciﬁc catabolic functions. Moreover, a large number of ﬁres (4 ﬁres in 57 years compared to 1–2) resulted in lasting degradation of the relative intensity of methyl C function in polymethylene, O-Alkyl C, aromatic C and phenolic C functions inducing a slow-down in recovery of microbial properties. These results also conﬁrm our hypothesis that some chemical functions of SOM can be in equilibrium with wildﬁre history. Finally, this research demonstrates that FT-NIR analysis can be used as a valuable tool to assess both the wildﬁre history and the vulnerability of soil quality to shifts in historical ﬁre regimes
Keywords: 13C NMR; Biolog; Catabolic evenness; Fire recurrence; FT-NIR spectroscopy; Recovery

Old-field secondary succession in SE Spain: can fire divert it? - Santana, Victor M; Jaime Baeza, M; Marrs, Rob H; Ramón Vallejo, V (Plant Ecology, 2010)
In the Mediterranean Basin, most cultivated areas were abandoned in the last century and are now in various stages of old-ﬁeld succession. The aim of this work was to analyse the successional trajectories of these ecosystems, and to assess possible deviations in these pathways due to ﬁre occurrence at high or low recurrence levels. Old-ﬁelds abandoned either about 50 or about 100 years ago were selected in SE Spain. Within the 50-year-old abandoned ﬁelds, plots were established which had been burned by 1, 2 and 3 ﬁres in the last 25 years. Cover values of vascular species were sampled and then analysed by means of multivariate analysis. Euclidean distances between resulting communities were used as an indicator of the possible deviation from the unburned successional pathway. Our results pointed to the possibility that different successional pathways may exist depending on ﬁre occurrence and recurrence. In the absence of ﬁre, the vegetation is dominated by pioneer species, mainly Pinus. With the passage of time this vegetation will become dominated by later successional tree species (Quercus). However, when early-successional communities are affected by ﬁre, the succession can be diverted. A single ﬁre is enough to change Pinusforests into alternative stable states dominated by Rosmarinus ofﬁcinalis shrub communities, where the colonisation of species in later successional stages is arrested. This deviation increases in high ﬁre recurrence regimes where the vegetation changes to dwarf shrubs and herbs.
Keywords: alternative stable state; Arrested succession; CCA; Fire recurrence; Mediterranean vegetation; Successional pathway